2019
DOI: 10.1001/jamacardio.2019.1180
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Time Between Left Ventricular and Aortic Systolic Pressure Peaks With Severity of Aortic Stenosis and Calcification of Aortic Valve

Abstract: Diagnosis of low-gradient severe aortic stenosis (AS) is challenging. We hypothesized that the time between left ventricular (LV) and aortic systolic pressure peaks (T LV-Ao) is associated with aortic stenosis (AS) severity and may have additive value in diagnosing severe AS, especially in patients with low-gradient AS. OBJECTIVE To investigate the diagnostic utility of measuring catheter-based T LV-Ao in patients with severe AS. DESIGN, SETTING, AND PARTICIPANTS We studied 123 patients with severe AS at the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Delayed AT and prolonged ET measured by echocardiography are associated with severity of AS. [ 16 ] AT/ET has been found to be relatively flow-independent. [ 17 ] We obtained a 43.3% disparity with AT/ET ratio pointing toward its flow dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed AT and prolonged ET measured by echocardiography are associated with severity of AS. [ 16 ] AT/ET has been found to be relatively flow-independent. [ 17 ] We obtained a 43.3% disparity with AT/ET ratio pointing toward its flow dependency.…”
Section: Discussionmentioning
confidence: 99%
“…We recently shown that prolonged AT/ET is a valuable parameter to predict mortality in unselected patients with at least moderate AS, with a prognostic cut-off value of 0.36 9 . Sato et al have recently shown that prolonged time between left ventricular and aortic systolic pressure peaks measured by left cardiac catheterization is associated with SAS according to aortic valve calcification scoring, including a subgroup of patients with LG-SAS 22 . To the best of our knowledge, no study has specifically studied the relationship between AT/ET ratio and outcome in patients with LG-SAS and preserved EF.…”
Section: Discussionmentioning
confidence: 99%
“…The new cerebral ischemic lesions were evaluated in DWI sequence, fluid-attenuated inversion recovery sequence, and apparent diffusion coefficient maps by two independent authors, and they were confirmed by a neurologist. The analysts only knew that the patients underwent TAVI and their basic information such as the patient’s name and gender, without knowing the patient’s anatomical data (including echocardiographic and CT characteristics) and procedural data [ 15 ]. The volume of CILs was analyzed in DWI sequence using MRIcron software Version 4 (NeuroImaging Tools and Resources Collaboratory, South Carolina).…”
Section: Methodsmentioning
confidence: 99%